1998
DOI: 10.1093/emboj/17.7.1973
|View full text |Cite
|
Sign up to set email alerts
|

Btk/Tec kinases regulate sustained increases in intracellular Ca2+ following B-cell receptor activation

Abstract: Bruton's tyrosine kinase (Btk) is essential for B‐lineage development and represents an emerging family of non‐receptor tyrosine kinases implicated in signal transduction events initiated by a range of cell surface receptors. Increased dosage of Btk in normal B cells resulted in a striking enhancement of extracellular calcium influx following B‐cell antigen receptor (BCR) cross‐linking. Ectopic expression of Btk, or related Btk/Tec family kinases, restored deficient extracellular Ca2+ influx in a series of nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
332
1
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 377 publications
(367 citation statements)
references
References 97 publications
33
332
1
1
Order By: Relevance
“…[11]. A similar profile of calcium flux to that described here was observed in A20 cells expressing a dominant negative form of Syk [33].…”
Section: Resultssupporting
confidence: 81%
“…[11]. A similar profile of calcium flux to that described here was observed in A20 cells expressing a dominant negative form of Syk [33].…”
Section: Resultssupporting
confidence: 81%
“…3B). Similar ®ndings were reported in the XLA cell lines [22], while in the Btk de®cient DT 40 cells, the BCR-induced tyrosine phosphorylation of PLCg2 was reduced [20]. The fact that several studies have suggested that PLCg is a substrate for Btk [20,22,23], could argue for compensating kinase elements (i.e.…”
Section: Bcr-induced Plcg Tyrosine Phosphorylation Is Normal In Btk Msupporting
confidence: 79%
“…However, our failure to 34 J. Forssell et al detect PEt formation upon BCR stimulation, although readily detectable using phorbol esters, argues that the PA we detected in our experimental set-up was not derived from a PLD-activity, but rather from PLC mediated PI-hydrolysis. Reduced PI-turnover is also detected in human XLA cell-lines [22], xid B cells [24] and TCR stimulated mouse CD4 T cells de®cient for Itk (another member of the Btk family) [50], suggesting that regulation of PI-hydrolysis could be a general property of the Btk/Tec/Itk family kinases.…”
Section: Bcr-induced Plcg Tyrosine Phosphorylation Is Normal In Btk Mmentioning
confidence: 97%
See 2 more Smart Citations